Penerapan Manajemen Risiko pada Usaha Penggilingan Padi di Desa Karangwuluh - Nida Aufa Al ‘Asya; Amirah, Amirah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the level of risk management implementation in rice milling enterprises in Karangwuluh Village, Suradadi District, Tegal Regency. The rice milling sector plays a strategic role in supporting rural economic sustainability by transforming agricultural produce into value-added products. However, this activity faces various risks originating from internal factors such as machine breakdowns, operational errors, and declining rice quality, as well as external factors such as price fluctuations, unstable paddy supply, and extreme weather conditions. The research employed a quantitative descriptive method with a survey approach involving four active rice milling business owners through a Likert-scale questionnaire. Data were analyzed using descriptive statistics to measure the level of risk management implementation across three key variables: risk identification, risk evaluation and measurement, and risk management. The results revealed that the overall implementation level was categorized as high to very high, with average scores of 4.50 for risk identification, 4.475 for risk evaluation and measurement, and 4.00 for risk management. The entrepreneurs demonstrated high awareness of potential risks and the ability to evaluate them systematically, although record-keeping and financial management aspects still require improvement. In conclusion, risk management implementation in the rice milling enterprises of Karangwuluh Village has been effective; however, strengthening administrative and financial preparedness is necessary to ensure long-term business sustainability.